2014
DOI: 10.1017/s0022215114002540
|View full text |Cite
|
Sign up to set email alerts
|

Investigation ofATP6V1B1andATP6V0A4genes causing hereditary hearing loss associated with distal renal tubular acidosis in Iranian families

Abstract: ATP6V1B1 genetic mutations were detected in more than half of the families studied. Mutations in this gene therefore seem to be the most common causative factors in hearing loss associated with distal renal tubular acidosis in these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The prevalence of hearing loss was higher in the ATP6V1B1 mutations, and patients with ATP6V1B1 mutation had statistically significantly higher PTAs than patients with ATP6V0A4 mutation. These findings are consistent with previous reports noted that hearing loss is more severe in ATP6V1B1 mutations than in ATP6V0A4 mutations [Karet et al, 1999a;Stover et al, 2002;Gao et al, 2014;Zeinali et al, 2014]. In previous reports, ATP6V1B1 mutations were associated with early-onset hearing loss, whereas ATP6V0A4 mutations were associated with lateonset hearing loss [Karet, 2002;Stover et al, 2002].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of hearing loss was higher in the ATP6V1B1 mutations, and patients with ATP6V1B1 mutation had statistically significantly higher PTAs than patients with ATP6V0A4 mutation. These findings are consistent with previous reports noted that hearing loss is more severe in ATP6V1B1 mutations than in ATP6V0A4 mutations [Karet et al, 1999a;Stover et al, 2002;Gao et al, 2014;Zeinali et al, 2014]. In previous reports, ATP6V1B1 mutations were associated with early-onset hearing loss, whereas ATP6V0A4 mutations were associated with lateonset hearing loss [Karet, 2002;Stover et al, 2002].…”
Section: Discussionsupporting
confidence: 93%
“…The association between dRTA and hearing loss was first reported by Royer andBroyer in 1967 [Royer andBroyer, 1967]. Since then, hearing loss with different characteristics in ATP6V0A4 and ATP6V1B1 mutations has been reported in many studies [Gil et al, 2007;Aksakal et al, 2009;Gao et al, 2014;Zeinali et al, 2014]. More recent studies have also reported hearing loss in FOXI1 mutations associated with dRTA [Enerbäck et al, 2018].…”
Section: Introductionmentioning
confidence: 93%
“…As expected, none of patients harboring SLC4A1 gene defects had deafness because the Cl − /HCO3 − anion exchanger does not express in the ears. It was classically assumed that dRTA caused by defective ATP6V1B1 gene was associated with early nerve hearing loss [7,28,[30][31][32][33], while ATP6V0A4 mutations were related with either late-onset deafness or normal hearing, [34][35][36][37][38][39][40]. Vargas-Poussou et al [41] challenged this assumption demonstrating genetic heterogeneity in dRTA associated with deafness and emphasizing the importance of mutational gene analysis for recessive forms of dRTA independent of Fig.…”
Section: Discussionmentioning
confidence: 99%